Designing healing garden and restorative outdoor space for old folk’s at senior citizens complex Seksyen 24, Shah Alam - Za’ini, Nurul Izzati (2018)
Healing gardens are frequently connected to the open space related to healthcare group or area that the purpose is to increase the people well-being. This topic mostly related to the elder population and it can be a healing garden when the gardening activity can improve a healthy lifestyle. The purpose of this study is providing a well-design of outdoor space as a remedial and recuperative a healthy environment for old folk’s community at Senior Citizens Complex Section 24, Shah Alam. The target user for this project study is a men because of the study and some research with the resident at Seksyen 24, Shah Alam shows the total of elderly men mostly need a healthcare than women. The methodology of this study involves the implementation stages of secondary data from government department and existing data from previous researches which already published. The primary data has been identified through observation and data recorded method. All collected data are synthesised to identify the potential area to be developed and preserved. Based on strategies and design ideas inspired from the concept of “ Zamrud ” that has been transform into physical form in designing the open spaces to be more functional, systematic, accessible and conservation of natural features to make the place more authentic with their own identity. The finding of this study will produce a master plan which consist of all solution and mechanism in order to achieve the design goal. This study will be significant to promote therapeutic landscape design to improve quality of life of the old folk’s community.